High-Current Sensing Technology for Transparent Power Grids: A Review - Hongyu Sun; Songling Huang; Lisha Peng (IEEE Open Journal of the Industrial Electronics Society)
The global energy industry is moving toward a trend of green and low-carbon transformation. A transparent power grid represents a new development form under this energy transition trend, integrating the power grid with new generation information and communication technologies, exemplified by the Internet. The use of micro smart sensors allows real-time monitoring of many important parameters of power systems via current, which is crucial for ensuring safe, stable, intelligent, and green power grid operation. Here, based on the development logic of current sensing technology for traditional-smart-transparent power grids, we focus our research on high-current sensing in a transparent power grid. First, we review the widely used traditional current sensing methods of shunts and Rogowski coils. More advanced optical fiber current sensing methods and microelectromechanical system current sensing chips are then introduced, which are more suitable for the smart sensing requirements of transparent power grids. In addition, we present and discuss the technical characteristics, research status, application scope, advantages and disadvantages, and future development directions of the above methods in detail. Finally, we address many essential challenges, including miniaturization, integration, low power consumption, passive wireless sensing, long-range operation, and complex environmental parameters in the comprehensive intelligent and transparent sensing of current parameters in power grids. To address these challenges, we present three possible development directions: sensor improvement, development of communication and networking technologies for sensors, and the advancement of intelligent and fast processing methods through communication.